A case of chronic suppurative otitis media caused by Kerstersia gyiorum. Issue 11 (25th August 2015) - Uysal, Elif B.; Çelik, Cem; Tuzcu, Nevin; Can, Fevzi; Doğan, Mansur; Ertürk, Rahşan; Bakici, Mustafa Z.
<x xml:space="preserve">Abstract</x> Chronic suppurative otitis media is inflammation of the middle ear and mastoid that involves discharge and hearing loss. Kerstersia gyiorum is a member of the Alcaligenaceae family that who could not be treated with classical treatments such as patients with chronic otitis media, neck abscesses. K. gyiorum strain isolated from a patient with chronic suppurative otitis media.